2011
DOI: 10.4139/sfj.62.702
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Expansion Properties of Invar Alloy Electrodeposits

Abstract: インバー合金電析膜の熱膨張特性 山本 貴代Thermal expansion properties of Invar (Fe-36 mass%Ni) alloy electrodeposits were investigated. The Fe-36 mass%Ni alloy electrodeposits from sulfate/chloride electrolytes using additives, saccharin sodium, and malonic acid. The electrodeposits, of about 150 μm thickness, had no crack. The thermal expansion curve showed that contraction of the electrodeposits occurred in the 270-420 ℃ range during first heating. During the first cooling and second heating, it showed the same behavior as that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 2 publications
2
23
0
Order By: Relevance
“…The CTE of the electroformed Fe-Ni alloy metal mask after annealing was approximately 3 ppm/°C and was four times less than that of the conventional electroformed Ni and Ni-Co alloys. We propose that the reduction of the CTE of the electroformed Fe-Ni alloy metal masks after annealing was because of the phase transition from bcc to fcc, as reported in references [4], [5], and [7-9].…”
Section: -3 / T Nagayamamentioning
confidence: 69%
See 2 more Smart Citations
“…The CTE of the electroformed Fe-Ni alloy metal mask after annealing was approximately 3 ppm/°C and was four times less than that of the conventional electroformed Ni and Ni-Co alloys. We propose that the reduction of the CTE of the electroformed Fe-Ni alloy metal masks after annealing was because of the phase transition from bcc to fcc, as reported in references [4], [5], and [7-9].…”
Section: -3 / T Nagayamamentioning
confidence: 69%
“…For the temperature range between 300 °C and 400 °C, the Fe-Ni alloy electroformed metal mask had a negative CTE. This phenomenon was considered to be caused by an increase in the atomic packing density (contraction) because of a phase transformation from metastable body-centered cubic (bcc) phases to equilibrium face-centered cubic (fcc) phases [4,5,[7][8][9] and reduction of the defects (contraction) because of the recrystallization of the Fe-Ni alloy electroformed metal mask by heating [4,5,7]. Furthermore, for temperatures above 400 °C, a rapid increase in the length of the specimen was detected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a temperature range of 573 to 673K, the Fe-Ni alloy electroformed metal mask had negative CTEs. It is considered that this phenomenon originates in increase of the atomic packing density (contraction) by the phase transformation from bcc phases to fcc phases (4,6,7,8) and reduction of defects (contraction) by a recrystallization of the Fe-Ni alloy electroformed metal mask by heating (4,6). Furthermore, for above 673K, rapid increase of the length of the specimen was measured.…”
Section: Resultsmentioning
confidence: 99%
“…In the invar composition range, the CTE of the pyrometallurgically produced Fe-Ni alloys were exhibited lower values for the equilibrium fcc phase [14]. In addition, we have reported that in the electrodeposited Fe-Ni alloy with 36-42 wt% Ni the heat treated deposits were transformed from metastable bcc phases to equilibrium fcc phases and had lower CTEs than the as-deposits [13,[15][16]. While the electroless deposited Fe-36 wt%Ni alloy film have a moderate CTE for ceramics, the CTE was higher than that of a pyrometallurgically produced Fe-36 wt%Ni alloy ; this can probably be attributed to the fact that the alloy phase of the electroless deposited films obtained included a bcc phase.…”
Section: Crystal Structure Of the Electroless Deposited Fe-ni Alloy Fmentioning
confidence: 93%